QUERI GANDA PADA SISTEM TEMU-KEMBALI INFORMASI BERBASIS JARINGAN INFERENSI - Wisnani, Yahma (UI Scholars Hub, 2004)
The Multiple Query of Information Retrieval System Based on Inference Network. The multiple query is a query that combines Boolean and probabilistic query on the information retrieval inference network system, the system consists of two components i.e. a dokument and a query network, they are joined by links between the representation and query concepts. The document network build an inverted belief list and the query network are evaluated by using canonical matrix. The similarity process between representation and query conceps yields a set of relevant document retrieved. The experiment has showed that the use of multiple query formulations will significantly improve the retrieval perfomance, compared to either the Boolean or probabilistic query